Efektivitas Variasi Ketebalan Zeolit dan Pecahan Genteng dalam Menurunkan Kadar Fe dan Mn Air Sumur Gali Dusun Waru Rangkang di Sapen, Manisrenggo, Klaten - Fitri Maryani; Purwanto Purwanto; Abdul Hadi Kadarusno (Sanitasi: Jurnal Kesehatan Lingkungan, 2015)
Water has very important function for human’s life. Clean water contaminated by chemical substances, for instance iron and manganese, can cause serious health problems. Iron and manganese concentration in water can be reduced by using ion exchange medium, such as zeolite and tile particles. The objective of the study was to discover the thickness variation of both mediums which is most effective for decreasing the concentration of iron and mangane in dig well water at Waru Rangkang Village of Sapen, Manisrenggo, Klaten, by conducting an experiment with pre-test post-test with control group design. There were three thickness variation, i.e. Filter A, composed of 60 cm zeolite and 60 cm tile particle; Filter B, composed of 80 cm zeolite and 40 cm tile particle; and Filter C, composed of 40 cm tile particle and 80 cm zeolite. The water source used in ths experiment was one well with high concentration of iron and manganese, belong to one villager. The source water was taken by using grab sampling method for six replications. The data showed that Filter A, B and C, were able to reduce the iron concentration, as much as 78,76 %, 85,51 %, and 75,77 %, respectively; and were also able to reducethe manganese concentration 78,46 %, 79,50 %, dan 77,73 %. The results of data analysis with one way anova test at 5 % level of significance, identified that the reduction differences were statistically significant and the subsequent LSD test concluded that Filter B was the most effective.